Dynamic traffic balancing scheme for LB-BvN to guarantee in-order packet delivering - HU Hong-chao; GUO Yun-fei; PANG lin; BU You-jun (Tongxin xuebao)
Due to its outstanding extensibility performance,the LB-BvN switch had attracted much attention recently in the switching technology academia.However,the problem that it might disturb the sequences of packets made it not so applicable in practice.To overcome this,the principles for guaranteeing packets in order switching were first discussed.Then,based on these principles,it focused on research on the transmission characteristics in network traffic and came up with DFA and DFS algorithms.DFA assigned the switching paths to each flow based on their transport layer parameters to make sure that each packet in the flow were in order.DFS was more sophisticated than DFA in that it first divided flows into flowlets.In this way,the flowlets in the flows were in order.Both DFA and DFS could achieve in order packets switching with limited flow states maintained in the line-cards.Simulation results show that both DFA and DFS can achieve good performance.